Peningkatan Prestasi Belajar Membaca dan Menulis Melalui Penggunaan Alat Peraga pada Siswa Kelas 1 SDI Wolowona 1 - Adelfrida Kemba (Ekspektasi: Jurnal Pendidikan Ekonomi, 2019)
Improving the quality of basic education, especially in elementary schools, has become a government policy, which must be implemented and realized as well as possible. This effort is carried out in order to improve the quality of human resources.One of the main emphases in the purpose of basic education is that primary school graduates master "Calistung", this is so that the emphasis on learning to read, write and count becomes the main key in the learning process. To obtain optimal results, the quality improvement of education must be pursued in a planned and gradual manner. Many of the techniques adopted by teachers in an effort to improve reading achievement on their students, one of the techniques adopted is that learning to read in the early grades should always look for the right methods and techniques.Reading activities for students are very important, this is due to the fact that the learning aspect of Indonesian is a unified whole which includes listening, speaking, telling stories, reading, telling stories, and writing, so that if one aspect is not taught then Indonesian language learning is incomplete. The research method used is action research by determining the steps: planning, action implementation procedures, reflection, research subjects, data collection, research instruments, technical data analysis, participant preparation, action research using a spiral path with two cycles.The results of the research from cycle I and cycle II of the data collected showed a significant increase in achievement, so that. it can be concluded that through teaching aids reading achievement in students can be improved.